'It felt like there was always someone there for us': Supporting children affected by domestic violence and abuse who are identified by general practice. (7th May 2021) - Roy, Jessica; Williamson, Emma; Pitt, Katherine; Stanley, Nicky; Man, Mei‐See; Feder, Gene; Szilassy, Eszter
Abstract: One in five children in the UK are affected by domestic violence and abuse. However, primary care clinicians (GPs and nurses) struggle to effectively identify and support children and young people living in homes where it is present. The IRIS+ (Enhanced Identification and Referral to Improve Safety) training and advocacy support intervention aimed to improve how clinicians respond to children and young people affected by domestic violence and abuse. IRIS+ training was delivered as part of a feasibility study to four general practices in an urban area in England (UK). Our mixed method design included interviews and questionnaires about the IRIS+ intervention with general practice patients, including children and young people as well as with clinicians and advocacy service providers. We collected the number of identifications and referrals by clinicians of children experiencing domestic violence and abuse through a retrospective search of medical and agency records 10 months after the intervention. Forty‐nine children exposed to domestic violence and abuse were recorded in medical records. Thirty‐five children were referred to a specialist domestic violence and abuse support service over a period of 10 months. Of these, 22 received direct or indirect support. The qualitative findings indicated that children benefitted from being referred by clinicians to the service. However, several barriers at the patient and professional level prevented children and young people from being identified and supported. Some of these barriers can be addressed through modifications to professional training and guidance, but others require systematic and structural changes to the way health and social care services work with children affected by domestic violence and abuse.